2005
DOI: 10.1111/j.1440-1819.2005.01332.x
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation and eating disorders in Asian and Caucasian Australian adolescent girls

Abstract: The present study aimed to compare the attitudes and psychopathology of eating disorders between Asian and Caucasian adolescent girls; and investigate the relationship between acculturation and the attitudes and psychopathology of eating disorders in subgroups of Asian girls. Two groups of non-clinical adolescent girls in Perth, Western Australia, were compared using a survey method. There were 17 Asian and 25 Caucasian adolescent girls, aged 14-17 drawn from private high schools in Perth who were screened usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
(47 reference statements)
1
13
0
1
Order By: Relevance
“…A further important finding was that there were no statistically significant differences in disordered eating scores across the different WCI groups. This finding is consistent with previous findings, in which Asian American ( Marques et al, 2011 ; Nouri et al, 2011 ), and Australian women ( Jennings et al, 2006 ) demonstrated comparable levels of weight concerns, the use of unhealthy weight control behaviors and eating pathology compared to Caucasian women, but contradicts the findings of other studies, which found higher eating pathology in Asian females ( Jennings et al, 2005 ) compared to Caucasian Australians. Future studies are therefore required to disentangle these contradictory findings.…”
Section: Discussionsupporting
confidence: 90%
“…A further important finding was that there were no statistically significant differences in disordered eating scores across the different WCI groups. This finding is consistent with previous findings, in which Asian American ( Marques et al, 2011 ; Nouri et al, 2011 ), and Australian women ( Jennings et al, 2006 ) demonstrated comparable levels of weight concerns, the use of unhealthy weight control behaviors and eating pathology compared to Caucasian women, but contradicts the findings of other studies, which found higher eating pathology in Asian females ( Jennings et al, 2005 ) compared to Caucasian Australians. Future studies are therefore required to disentangle these contradictory findings.…”
Section: Discussionsupporting
confidence: 90%
“…Supporting this are reports from Britain and Australia that less acculturated Asian girls have unhealthier attitudes and psychopathology towards eating. 12,13 Published literature on eating disorders in AsianAmericans has mostly focused on adults, issues of body dissatisfaction and acculturation. Assessment of eating pathology among adolescents has been limited to data from community samples.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent studies using the EAT-26 [3] and the EDI-II [2] to investigate attitudes and psychopathology of eating disorders have produced results that are somewhat different between Asian and Caucasian adolescent girls [31, 32]. Furthermore, studies comparing Japanese adolescents with North Americans and Europeans in terms of drive for thinness and body dissatisfaction have reported mixed findings; one group [33] found that female Japanese without eating disorders reported higher levels of drive for thinness and body dissatisfaction than their German counterparts, whereas another group [30] found lower levels of drive for thinness and body dissatisfaction among Japanese than among a North American-referenced comparison.…”
Section: Introductionmentioning
confidence: 99%